2020
DOI: 10.1002/mus.26903
|View full text |Cite
|
Sign up to set email alerts
|

Spinal muscular atrophy care in the COVID‐19 pandemic era

Abstract: The coronavirus disease 2019 pandemic has resulted in reorganization of healthcare settings affecting the delivery of clinical care to patients with spinal muscular atrophy (SMA). There is a concern that patients with SMA may be at increased risk of manifesting severe symptoms of COVID-19. Currently approved therapies for SMA improve survival and motor function; however, their delivery requires an increased exposure to the health system and a dedicated healthcare team. In this study, we discuss consensus reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 17 publications
1
44
0
1
Order By: Relevance
“…A higher dose, and therefore higher CSF drug levels, may potentiate nusinersen efficacy in patients who were described as non-responders in this study. It has already been reported that higher nusinersen CSF exposure correlated with greater increase in motor outcome scales as well as greater decline in neurofilament levels [ 28 ]. However, potential concordant increasing side effects need to be taken into account [ 2 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher dose, and therefore higher CSF drug levels, may potentiate nusinersen efficacy in patients who were described as non-responders in this study. It has already been reported that higher nusinersen CSF exposure correlated with greater increase in motor outcome scales as well as greater decline in neurofilament levels [ 28 ]. However, potential concordant increasing side effects need to be taken into account [ 2 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent expert consensus 69 promotes timely and consistent treatment for spinal muscular atrophy whenever possible to yield better outcomes. Adherence to nusinersen dosing timeline is important; missed doses should be given as soon as possible, and the original schedule resumed.…”
Section: Management Of Neurologic Diseases In the Covid-19 Pandemicmentioning
confidence: 99%
“…In the case of nusinersen (intrathecal administration with a loading dose of 4 doses the first 2 months and then every 4 months), it has been reported that the delay of 1 month without medication leads to a 10% reduction of the drug in CSF. If there is a delay in administration, the schedule should not be readjusted, but rather follow initial proposed calendar to ensure optimal intrathecal medication levels (34).…”
Section: Treatmentmentioning
confidence: 99%